Enhancement of surface potential buildup and decay of tris(8-quinolinato)aluminum film deposited on ultraviolet/ozone-treated gold electrodes - Kajimoto, N.; Muhamad, M.R.; Rahman, Saadah Abdul; Manaka, T.; Iwamoto, M. (IOP Publishing, 2005)
The enhancement of the surface potential of tris(8-quinolinato)aluminum (Alq3) film deposited on ultraviolet (UV)/ozonetreated gold electrodes was confirmed by surface potential measurement, and the ordering of molecular dipoles was suggested. The enhanced surface potential of the order of 10 V decayed rapidly by photo irradiation, due to molecular dipole disordering, but a surface potential of 100-400mV remained. Interestingly, this remaining surface potential of Alq3 on the UV/ozonetreated gold electrode was always smaller than that of Alq3 film on an untreated gold electrode. It was concluded that the UV/ozone treatment is effective in decreasing the density of surface states at the Alq3-metal interface as well as for the enhancement of molecular dipole ordering.